1998
DOI: 10.1006/jmbi.1997.1499
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the lysozyme from bacteriophage lambda and its relationship with V and C-type lysozymes

Abstract: Like other lysozymes, the bacteriophage lambda lysozyme is involved in the digestion of bacterial walls. This enzyme is remarkable in that its mechanism of action is different from the classical lysozyme's mechanism. From the point of view of protein evolution, it shows features of lysozymes from different classes.The crystal structure of the enzyme in which all tryptophan residues have been replaced by aza-tryptophan has been solved by X-ray crystallography at 2.3 Å using a combination of multiple isomorphous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 46 publications
5
60
0
Order By: Relevance
“…A structure similarity search using the Dali server did not return any structures with significant similarity to the PGT domain. However, a secondary structure matching (SSM) search returned bacteriophage -lysozyme ( R; also known as LaL), which breaks the ␤(1,4) glycosidic linkages between NAM and NAG residues of peptidoglycan, the same bonds that the PGTs make (14,15). Terrak et al (16) have previously suggested that the PGTs might resemble the lysozymes.…”
Section: Resultsmentioning
confidence: 99%
“…A structure similarity search using the Dali server did not return any structures with significant similarity to the PGT domain. However, a secondary structure matching (SSM) search returned bacteriophage -lysozyme ( R; also known as LaL), which breaks the ␤(1,4) glycosidic linkages between NAM and NAG residues of peptidoglycan, the same bonds that the PGTs make (14,15). Terrak et al (16) have previously suggested that the PGTs might resemble the lysozymes.…”
Section: Resultsmentioning
confidence: 99%
“…The side chain of Trn73 is oriented outwards while that of Trn74 is completely buried, as shown in Table 1. In the interaction between molecules A and C in one column, the two clefts interpenetrate each other in a very symmetrical way, as previously described (Evrard et al, 1998). Since Trn73 is located close to the entrance to this cleft, it can be expected that the packing between the two molecules will considerably modify the accessibility of this side chain in molecules A and C. Indeed, Table 1 shows that when the two molecules are considered together, the accessible surface of the N 2 atoms is practically reduced to zero and the total accessibility of the residues is considerably lowered.…”
Section: Methodsmentioning
confidence: 70%
“…Synchrotron data at 2.3 A Ê were collected on beamline X31 at EMBL c/o DESY (Evrard et al, 1997). Solution of the crystal structure (Evrard et al, 1998) revealed the presence of three independent molecules in the asymmetric unit. The molecules are essentially composed of two domains connected by a long helix (H3).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations